The Impact of Social Media Marketing on Brand Loyalty: The Role of Brand Trust and Brand Equity as Mediating Variables - Sutomo Sutomo; Sumardi Sumardi; Lesna Purnawan; Unes Juhaeni (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The development of social media has significantly influenced the way companies establish relationships with their consumers, In an increasingly competitive environment, marketing strategies that involve direct interaction through digital platforms are becoming more crucial for building brand loyalty. This study aims to understand how promotional activities through social media can strengthen consumer loyalty, by considering brand trust and perceptions of brand value as mediating factors that connect these elements. After the raw data had been collected and analyzed through a process that included picking out active Instagram users, we selected those who have followed skincare brand accounts and bought products right after exposure to promotional information. Utilizing SmartPLS software for Structural Equation Modeling, it was found that the quality of a message, visual impact and social interaction represent the three factors which have great influence on whether trust is established or else there will be positive or negative evaluation for your brand. Trust, which builds up from good experiences and consistent communication, as it turns out leads to emotional connections. With these connections in place, it becomes easier to stick around and harder to leave–for repeated generic preferences over time. Also, perceptions of product value and quality serve as reinforcing factors in shaping repeat purchase decisions. The research findings suggest that successful marketing strategies can not only be based on the frequency of social media appearances, but should instead see how relationships are actively and authentically fostered. Enterprises that keep up two-way communication and give consistent experiences will have a better chance for higher customer loyalty. These findings lay a necessary groundwork for business practitioners to design digital approaches less reliant on random solitude and more enabled through social relationships.